2021
DOI: 10.35799/pha.10.2021.34044
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan Dan Penggunaan Antibiotik Secara Swamedikasi Pada Masyarakat Di Kota Manado

Abstract: Antibiotics are drugs to prevent and treat infections disease, the use of antibiotics must be in accordance with a doctor’s prescription therefore it is safe for patients. Improper use of antibiotics is often done in self-medication. Incorrect use of antibiotics will cause negative impacts, such as resistance to one or several antibiotics, increased drug side effect, expensive health care costs and even death. This research was conducted to determine the level of knowledge and behaviour of using antibiotics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
0
3
0
7
Order By: Relevance
“…Untuk menghindari hal-hal yang tidak diinginkan pada penggunaan antibiotika, diperlukan edukasi yang berkaitan dengan penggunaan antibiotika yang tepat agar tingkat pengetahuan dan pemahaman masyarakat tentang penggunaan antibiotika yang tepat dapat dicapai, sehingga tidak terjadi kesalahgunaan penggunaan antibiotika di kalangan masyarakat. Penyuluhan merupakan salah satu cara yang dapat dilakukan untuk meningkatkan pengetahuan bagi masyarakat (Wowiling et al, 2013).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Untuk menghindari hal-hal yang tidak diinginkan pada penggunaan antibiotika, diperlukan edukasi yang berkaitan dengan penggunaan antibiotika yang tepat agar tingkat pengetahuan dan pemahaman masyarakat tentang penggunaan antibiotika yang tepat dapat dicapai, sehingga tidak terjadi kesalahgunaan penggunaan antibiotika di kalangan masyarakat. Penyuluhan merupakan salah satu cara yang dapat dilakukan untuk meningkatkan pengetahuan bagi masyarakat (Wowiling et al, 2013).…”
Section: Pendahuluanunclassified
“…Penyuluhan dengan bertatap muka dan memberikan informasi secara langsung diharapkan dapat lebih efektif dibandingkan dengan tindakan penyuluhan melalui media massa atau pun selebaran. Keefektivan dari penyuluhan dapat diketahui dengan melakukan pengukuran tingkat pengetahuan yang dilakukan sebelum dan sesudah penyuluhan sehingga dapat diketahui perubahan tingkat pengetahuan masyarakat (Wowiling et al, 2013).…”
Section: Tahun 2023 [Jurnal Kreativitas Pengabdian Kepada Masyarakat ...unclassified
“…111 One study found that people without health insurance were more likely to selfmedicate than those with health insurance, 111 whereas another study reported the opposite. 104 The main reasons for self-medication included positive previous experience (54-82%), 102,104,109,112 selfmedication being practical (61-83%), 94 easy access from the pharmacy (71%), 102 and doctor visit being expensive (44-72%) 102,109 or unpractical (56%). 96 The main advisors to self-medicate included health care providers (51-83%), 100,103,104,109 family, relatives or friends (21-45%), 96,102,112 internet (71%), 115 or reliance on their own knowledge (71%).…”
Section: Knowledge Attitudes and Perceptions On Antibiotic Use Among ...mentioning
confidence: 99%
“…104 The main reasons for self-medication included positive previous experience (54-82%), 102,104,109,112 selfmedication being practical (61-83%), 94 easy access from the pharmacy (71%), 102 and doctor visit being expensive (44-72%) 102,109 or unpractical (56%). 96 The main advisors to self-medicate included health care providers (51-83%), 100,103,104,109 family, relatives or friends (21-45%), 96,102,112 internet (71%), 115 or reliance on their own knowledge (71%). 96 Antibiotic adherence levels were not associated with education level or employment status (2 studies).…”
Section: Knowledge Attitudes and Perceptions On Antibiotic Use Among ...mentioning
confidence: 99%
See 1 more Smart Citation